The Effect of Circular Marketing and Storynomics on Brand Awareness and Profit Improvement of MSMEs in Bogor - Sudirjo, Frans; Supriandi, Supriandi; Pahrijal, Rival (Westscience Press, 2025)
This study examines the impact of Circular Marketing and Storynomics on Brand Awareness and Profit Improvement among MSMEs in Bogor. A quantitative analysis was conducted with a sample of 160 MSME owners and managers, using a Likert scale survey and data analysis via Structural Equation Modeling (SEM-PLS 3). The results reveal that both Circular Marketing and Storynomics have a significant positive influence on Brand Awareness and Profit Improvement. Circular marketing enhances brand recognition by aligning marketing strategies with sustainable practices, while Storynomics improves profitability by fostering emotional connections with consumers through storytelling. The study underscores the importance of integrating sustainability and narrative-driven marketing strategies for MSMEs to enhance their market presence and profitability. These findings provide actionable insights for MSMEs aiming to thrive in competitive markets by adopting sustainable and innovative marketing practices.